IMPLEMENTASI REFLEKSOLOGI SEBAGAI TERAPI KOMPLEMENTER DALAM MANAJEMEN PASCAOPERASI - Zulva, Siti; Sriati, Aat; Suryaningsih, Chatarina; Dewi Amir, Mayasyanti; Yudistira, Andi; Umu Kulsum, Dewi (Yayasan Putra Sukamanah Sejahtera, 2026)
Surgical procedures can lead to various postoperative clinical problems such as pain, anxiety, nausea and vomiting, sleep disturbances, and fatigue, all of which require comprehensive management. Reflexology, as a non-pharmacological complementary therapy, has the potential to support postoperative management through stimulation of reflex points on the soles of the feet, hands, and ears. This study aims to synthesize scientific evidence regarding the effectiveness of reflexology as a complementary intervention in postoperative patient management. A systematic review was conducted following the PRISMA 2020 guidelines. Literature searches were performed in PubMed, Scopus, Web of Science, CINAHL, EBSCOhost, and the Cochrane Library for publications from January 2010 to December 2024. The inclusion criteria were determined using the PICO framework, and methodological quality was assessed using the JBI Critical Appraisal Tools. Out of 1,032 identified articles, 15 studies met the inclusion criteria (13 randomized controlled trials, 1 clinical trial, and 1 randomized study). The synthesis results indicate that reflexology significantly: (1) reduces postoperative pain intensity, (2) decreases anxiety levels, (3) stabilizes physiological/hemodynamic parameters, (4) improves sleep quality, and (5) reduces fatigue. These effects were consistently observed across various surgical procedures, including coronary artery bypass graft (CABG), abdominal surgery, hysterectomy, and cesarean section. Reflexology has the potential to serve as a safe, effective, and practical complementary intervention to support postoperative patient management. Further studies with multicenter designs, larger sample sizes, and more standardized protocols are recommended.